The role of endorsement and certification of food heritage determinants toward food identity formation / Adilah Md Ramli - Md Ramli, Adilah (2018)
This study empirically measuring the role of endorsement and certification of food heritage determinants toward the food identity formation. A mix method approaches using qualitative through interview (panel experts) and quantitative through questionnaire survey (public) are applied in this study. In obtaining the valuable insights and causal correlation between the variables of interest or investigated variables, eight panel experts the from the Malaysia National Heritage Department were interviewed while 898 public respondents in the Klang Valley areas comprises of the Federal Territory of Kuala Lumpur, Putrajaya, the Petaling district in Selangor (Shah Alam, Petaling Jaya and Subang Jaya), Gombak, Klang and Hulu Langat and their suburbs and adjoining cities and towns were successfully surveyed. As part of the objectives of the study, the qualitative information through interview was interpreted using the thematic analysis. For the quantitative data gathered, several predetermined tests (reliability), the descriptive (frequency and central tendency) and inferential statistical analyses were conducted. A path analysis using Partial Least Square (PLS) approach to the Structural Equation Modelling (SEM) was employed to confirm the research questions, research objectives and all the proposed hypotheses.